Where is the Growth Going to Come From?. Issue 1 (17th January 2018) - Ellis, Luci
Abstract : As the mining investment boom turned down and became a drag on growth, the question has often been asked: "Where is the growth going to come from?" Commentators started speaking of a growth "handover": if mining investment was not going to provide our growth, something else needed to. And for a while, particular non‐mining sectors did seem to pick up, to become in turn the new "engine of growth." However, this article argues that the underlying drivers of growth over the longer term do not depend on external triggers. Instead, they can be found in the "three Ps" – population, participation and productivity.